TRENDS IN THE FACTORS CAUSING DIVORCE IN SEMARANG RAYA IN 2023: A CORRESPONDENCE ANALYSIS APPROACH - Muhammad Riefky; Firli Azizah; Andi Indra Jaya (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2025)
An ideal marriage should be the foundation for a harmonious family relationship, yet many marriages end in divorce. This study aims to identify the trend patterns of divorce causes in Semarang Raya in 2023 using correspondence analysis. The research results show that the factors causing divorce vary by region. In Semarang Raya, economic factors dominate Grobogan Regency, while forced marriage factors are more frequently found in Kendal Regency. The analysis used Euclidean distance to reinforce the findings on the relationship between the factors causing divorce in each region. These findings can be used as a basis for designing more focused divorce prevention policies in accordance with the social and economic characteristics of each region.